Weaker conditions for inexact mutitpoint Newton-like methods - Argyros, Ioannis K; Magreñán, Á. Alberto; Moreno-Mediavilla, Daniel; Orcos, Lara; Sicilia, Juan Antonio (Journal of Mathematical Chemistry, 2020)
In this paper we study the problem of analyzing the convergence both local and semilocal of inexact Newton-like methods for approximating the solution of an equation in which there exists nondifferentiability. We will impose conditions, to ensure that the method converges, are weaker than in the ones imposed in previous results. The theoretical results shown in this study are applied to a chemical application in order to be proven.
Keywords: inexact Newton-like methods; unified convergence; nondifferentiable equation; weaker conditions; JCR; Scopus